Failure of Bilateral Diplomacy on Irian Barat (Papua) Dispute (1950-1954) - Siswanto Siswanto (Journal of Indonesian Social Sciences and Humanities, 2018)
Fundamentally, Irian Barat (Papua) dispute between The Netherlands Indonesia was a territorial conflict or an overlapping claim. The Netherlands as the former colonialist did not want to leave Irian Barat (Papua) or remained still in the region, meanwhile Indonesia as the former colony denied the Netherlands status quo policy in Irian Barat (Papua). Potential dispute of the Irian Barat (Papua) was begun in the Round Table Conference (RTC) 1949. There was a point of agreement in RTC which regulates status quo on Irian Barat (Papua) and it was approved by Head of Indonesia Delegation, Mohammad Hatta and Van Maarseven, Head of the Netherlands Delegation. As a mandate of the RTC in 1950s there was a diplomacy on Irian Barat (Papua) in Jakarta and Den Haag. Upon the diplomacy, there were two negotiations held by diplomats of both countries, yet it never reached a result. As a consequence, in 1954 Indonesia Government decided to stop the negotiation and searched for other ways as a solution for the dispute. At the present time, Jakarta-Papua relationship is relatively better and it is based on a special autonomy, which gives great authority to the Local Government of Papua.